Ship hull slamming analysis with smoothed particle hydrodynamics method. (August 2020) - Cheng, H.; Ming, F.R.; Sun, P.N.; Sui, Y.T.; Zhang, A-Man
Highlights: A robust WCSPH model is applied to deal with the water entry of the bow-flare ship section. The evolution laws of the free surface and spry jet are analyzed. The water entry of a three dimensional ship hull is simulated. Abstract: In the marine and ocean engineering area, the water-entry process is a typical problem of fluid-solid interaction, which involves complex phenomenon such as the large deformation of free surface and considerable structure movement. In this process, the predicting impact load and summarizing the evolution law of the free surface deformation have important reference significance for the hull structure design. To address this issue, numerical simulations are carried out using a robust Smoothed Particle Hydrodynamics (SPH) model. The accuracy of the present SPH model is firstly validated by simulating the water entry of bow-flare section in two and three dimensions, respectively. Then, we investigate the variation characteristics of impact load and the evolution of free surface during the entry of the bow-flare ship section with different roll angles ( θ = 0 ∘ ∼ 20 . 3 ∘ ). Attention is focused on the flow separating phenomenon and the spray jet on the free surface. Finally, the water entry of a three dimensional ship hull is simulated. The velocity and pressure of flow field are analyzed and some conclusions are drawn.